Experiences and perceptions of participants and staff involved in HIV research in Gugulethu, South Africa - Gomba, Yolanda (Department of Public Health and Family Medicine, 2020)
It is important to understand the experiences and perceptions of HIV research from the perspectives of persons who have either participated in or worked on HIV research in lowresource settings. Obtaining such information is important because research in low-resource settings presents several ethical challenges that result in the vulnerability of participants due to factors such as low literacy levels, high rates of food insecurity and unemployment. Conducting research on the aforementioned can help researchers to design studies that mitigate some of the ethical challenges associated with conducting HIV research in lowresource communities. This dissertation adds on to existing literature on the experiences and perceptions of HIV research participants and staff involved in HIV research in low-resource settings. This dissertation is divided into three parts. Part A (Research protocol) discusses the importance of evaluating research participants’ experiences and perceptions of HIV studies conducted in lowresource settings. The section also outlines the purpose of the study, research questions, methodology, ethical considerations, rigour, reimbursement and dissemination of results. Part B (Literature review) presents an overview of the literature on HIV research in low-resource settings, with a specific focus on: ethical challenges, factors that contribute to participants’ decisions to participate in HIV research and findings from other studies which examined experiences and perceptions of HIV research in low-resource settings. The section also identifies gaps in the existing literature. Part C (Journal article) presents the findings of the study and the implications thereof.